Implementasi Kreativitas Mahasiswa Melalui Pembuatan Kerupuk Ubi Talas - Aventus Purnama Dep; Modesta Aswinda; Dionisia Farida Tamala; Viktorianus Ippi; Ronaldus Don Piran; Ester Nurani Keraru (Unika Santu Paulus Ruteng, 2023)
The use of taro in the making of crackers is a new strategy to create added value economically. The goals of this program are to train students to create innovative and creative works that can support the enhancement of the added value of local products, first by opening up business opportunities, second by giving students the chance to start their own businesses before they graduate, and third by increasing the demand for taro crackers. Tools and materials, production strategies, product manufacturing procedures, team preparation, and marketing strategies and techniques are only a few of the approaches used to carry out the operations. In addition to producing additional value to meet household food demands, the practice of using taro to make crackers also produces economic benefits. In Manggarai Regency, East Nusa Tenggara, the raw material for this taro cracker product is fairly accessible. In addition, hardly many people exploit this taro as a business opportunity to develop cutting-edge solutions. In order to ensure the long-term viability of the taro cracker product industry, this can raise the value of this local food item as a stand-alone exceptional ingredient. While the taro cracker sales system employs both an individual and a collective strategy. Additionally, it uses a cash oliver delivery (COD) system and social media marketing techniques (Website, WA, Facebook, and Instagram)